2004
DOI: 10.1093/jb/mvh069
|View full text |Cite
|
Sign up to set email alerts
|

Induction of CD44 and MMP Expression by Hyaluronidase Treatment of Articular Chondrocytes

Abstract: In this study, the effects of fragmentation of the glycosoaminoglycans of the cell-associated matrix by hyaluronidase (HAase) on the expression of CD44 receptor and matrix metalloproteinase (MMP) mRNAs in cultured articular chondrocytes were examined. Chondrocytes, isolated from rabbit and bovine articular cartilage, were treated with bovine testicular HAase (0-200 units/ml) in the presence or absence of an antibody for CD44. The mRNA levels of CD44, CD44 variant (CD44v), MMPs (MMP-1, -3 and -9), and tissue in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(27 citation statements)
references
References 0 publications
1
25
0
1
Order By: Relevance
“…Next, we treated WT 44 cells with hyaluronidase. Hyaluronidase is known to generate hyaluronan oligosaccharides (17), which, in turn, can promote CD44 cleavage (20). Hyaluronidase treatment resulted in an increased expression of both CD44-CTF and the 38 kDa band (Fig.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Next, we treated WT 44 cells with hyaluronidase. Hyaluronidase is known to generate hyaluronan oligosaccharides (17), which, in turn, can promote CD44 cleavage (20). Hyaluronidase treatment resulted in an increased expression of both CD44-CTF and the 38 kDa band (Fig.…”
Section: Resultsmentioning
confidence: 97%
“…Our initial hypothesis was that hyaluronan binding to CD44 might promote Ret-induced transformation of Rat-1 cells. We tested this by treating MEN2A-transformed cells with bovine testis hyaluronidase, which disrupts extracellular hyaluronan-cell interactions (17). This treatment did not affect the anchorageindependent growth capability of the cells (data not shown).…”
Section: Resultsmentioning
confidence: 99%
“…What is clear from all the studies is that HA is lost from the articular cartilage in a coordinate fashion with the loss of aggrecan (16,19,20). Experimentally, we have tried to mimic the loss of HA and proteoglycan via the use of HA oligosaccharides to displace the pericellular matrix (21)(22)(23)(24) or with hyaluronidases to remove the HA-rich pericellular matrix (21,22,25). With both approaches we observe the induction of pro-catabolic state by the chondrocytes, one that includes the up-regulation of MMP2, -3, -9, and -13 (24 -28) as well as ADAMTS4 and ADAMTS5 (28).…”
mentioning
confidence: 99%
“…Although there is no consensus on the molecular mechanisms by which CD44 is linked to apoptosis (Hauptschein et al, 2005), HA fragments generated from the ECM by hyaluronidases stimulate HER2 and c-Src tyrosine kinase phosphorylation of cytoskeletal proteins, and Rho GTPase signaling, through desialylated CD44 receptor-specific networks (Ponta et al, 2003;Turley et al, 2002). As we observed in the present study, expression of CD44 itself may not change following ligand binding, depending on the cell type or basal level of CD44 expression (Ohno-Nakahara et al, 2004), but the observed increase in CD95 expression is consistent with transcription factor upregulation following HA fragment binding by desialylated CD44 (Fieber et al, 2004;Ohno et al, 2005). CD44 genes are annotated in fish, amphibian, and avian genomes, but our data establish for the first time that reptile cells also express a CD44 homolog, and further suggest that CD44-specific tyrosine kinase signaling networks are also conserved across vertebrate species.…”
Section: Discussionmentioning
confidence: 45%